(untitled) (Swiss Medical Weekly, 2015)
Exosomes are nanovesicles, generally 50 to 90 nm in diameter, that correspond to the intraluminal vesicles of the endosomal multivesicular bodies and are secreted upon fusion of multivesicular bodies with the plasma membrane. Their molecular content is highly selected and includes not only specific proteins and lipids, but also RNA species, such as messenger RNAs (mRNAs) and microRNAs (miRNAs), which are delivered and active in target cells. As they are released in body fluids, exosomes can shuttle molecules for long distances. In the CNS they have been shown to regulate neuronal development and regeneration, and to modulate synaptic functions. In neurodegenerative diseases, they have an important role in propagating neurotoxic misfolded protein from one cell to another and, as recent data show, possibly other molecules contributing to neurotoxicity. Some exosomal lipids such as gangliosides GM1 and GM3 enhance the aggregation of alpha-synuclein, and RNA exosomal cargo is also altered during pathologies such as Alzheimer’s disease, prion diseases and amyotrophic lateral sclerosis. The aim of this review is to focus on the regulation of CNS exosomal function and highlight pathways that might have a role in the neurodegenerative process. The identification of the novel exosomal molecules involved in neurodegenerative diseases could provide important insights into the pathogenesis and contribute to the finding of novel diagnostic biomarkers and therapeutic approaches.